Linguistic features of processes in teacher – student conversations in the memoir “teacher man” by frank mccourt in light of functional grammar - Nguyễn, Thị Ngọc Ly (2016)
This thesis aims to find out the linguistic realizations, semantic and syntactic features of processes in teacher-student conversations in the memoir Teacher Man by Frank McCourt, and to help Vietnamese students of English understand the processes in Functional Grammar. This qualitative study was based on the descriptive framework of Functional Grammar. The presentation of the qualitative information of processes in teacher-student conversations was illustrated with examples quoted from the memoir Teacher Man by Frank McCourt. It was conducted by analyzing the data taken from 103 conversations in the memoir Teacher Man. The teacher-student conversations were examined to discover the semantic and syntactic features in terms of processes used in teacher-student conversations in the memoir Teacher Man. The thesis was designed for an analysis of processes to help Vietnamese majors of English have a better understanding of Functional Grammar in general and processes in particular. The processes were explored in view of semantic and syntactic features that the teacher and students delivered in their conversations. Pedagogically, the research results can be of some helps for educators, lecturers, teachers and learners of English, in addition to those who are interested in teaching and learning, especially in processes in Functional Grammar.